Lone star law [large type] - Randisi, Robert J. (Wheeler Publishing, a part of Gale, a Cengage Company, 2021)
"A collection of twelve stories that celebrate the legendary Texas Rangers--from the greatest Western storyteller Louis L'Amour, along with Elmer Kelton, Rod Miller, Robert J. Randisi, L. J. Washburn, and many more. Explore the proud heritage of the elite Texas Rangers in these exhilarating, white-knuckled stories. From historical tales of outlaws and rustlers to modern thrillers of tracking serial killers with the latest technology, LONE STAR LAW is an outstanding collection of stories about delivering justice the Texan way."--Back cover.